The effect of education and implementation of “National Hospital Disaster Preparedness Plan” on an Iranian hospital preparedness: An interventional study - Beyramijam, Mehdi (J Educ Health Promot, 2019)
INTRODUCTION: Hospitals as the first place for injuries have to keep up and increase activities in emergency and disasters. Therefore, any hospital necessarily requires disasters plan to improve its preparedness. The aim of this study is to investigate the effect of education and implementation of “National Hospital Disaster Preparedness Plan (NHDPP)” on Vali Asr Hospital preparedness in Iran. METHODOLOGY: In a pre- and post-intervention study, NHDPP educated in five sessions, and it was used as a guide in the promotion of Vali Asr Hospital preparedness in Iran. The Iranian version of “Hospital Disaster Preparedness (HDP) assessment tool” was used to measure the hospital preparedness score. Finally, the quantitative data analyzed by using IBM SPSS Statistics for Windows, Version 22.0. Armonk, NY: IBM Corp. RESULTS: Before intervention, the HDP score was measured in total and in the nine dimensions of preparedness. But after the intervention, it increased, 33% in command and control dimension, 33% in communication, 21% in safety and security, 26% in triage, 36% in surge capacity, 24% in the continuity of vital services, 27% in human resources, 13% in support and supplies management, and 7% in post disaster recovery dimension. Furthermore, the total HDP score increased about 24.5% after the intervention. CONCLUSION: This study demonstrates that the “Iranian HDP plan” leads to improve the Vali Asr HDP score. Therefore, by planning and implementation of effective educational programs, it is possible to improve the hospitals' preparedness in Iran.